SLANG IN GENERATION ALPHA: A SOCIOLINGUISTICS STUDY OF SLANG USE ON TIKTOK - Kurnia Kurnia; Venyta Sinaga; Syalaisha Syafira Irwansyah; Viola Sasti Bizora L. Tobing; Selina Grace Kaizura Simbolon (YAYASAN PADHANG MANAH SIBYAN, 2026)
The increasing use of social media has influenced how children communicate in everyday interactions. Among Generation Alpha, TikTok has become a common space where new slang expressions are encountered, repeated, and adapted into daily speech. This study examines the types of slang used by Generation Alpha on TikTok and explores their perceptions toward the use of slang on the platform. Using a qualitative sociolinguistic approach, this study involved four participants aged 7 to 11 years. The data were collected through interviews based on two TikTok videos uploaded by the same account, @kikisherly, which contain several Gen Alpha slang expressions. The interview data were analyzed through thematic coding and linguistic categorization to identify patterns of slang usage and perception. The findings show that Generation Alpha frequently uses internet-based slang such as sigma, mewing, and ayo bet, which are mainly acquired through imitation and informal language practices. The participants generally view slang as enjoyable and socially meaningful, although their understanding of the original meanings varies. These findings suggest that exposure to TikTok content shapes how slang is recognized and used by Generation Alpha in both online and offline contexts.